2021
DOI: 10.3130/aija.86.2257
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Effect of Green Design Office

Abstract: In this study, the authors conducted the experiment in the virtual environment to verify the physiological restorative effect of the Green Design Office. As a result, when the conventional design office has changed into the Green Design Office, the averages of standardized SCL values significantly increased (p<.01). Moreover, it was suggested that the increase of the restorative effect of arousal level was more obvious when the workers were aware of the Green Design Office. Those results indicate that it is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Meanwhile, the effects of Bartlett's spherical check confirmed that the magnitude p-value was once 0.000 ***, which confirmed value at that level, that the authentic speculation was once rejected, that there was once correlation between the variables, and that the issue evaluation was once legitimate to the extent that it used to be suitable. Research on restorative theory suggests that the premise of "restoration" is that the individual is in a "depleted" state, emphasizing the process of returning from a negative state to a natural state [58]. Taking nine typical sound sources in the Huohuoshan Forest Park area of Guangzhou as an example, the compatibility, coordination and attractiveness of each sound source were classified according to the median (IQR) and mean (SD) of the restorative perceptual evaluation of the compatibility, coherence and attractiveness of the various types of sound sources, as shown in Table 6.…”
Section: Validity Analysismentioning
confidence: 99%
“…Meanwhile, the effects of Bartlett's spherical check confirmed that the magnitude p-value was once 0.000 ***, which confirmed value at that level, that the authentic speculation was once rejected, that there was once correlation between the variables, and that the issue evaluation was once legitimate to the extent that it used to be suitable. Research on restorative theory suggests that the premise of "restoration" is that the individual is in a "depleted" state, emphasizing the process of returning from a negative state to a natural state [58]. Taking nine typical sound sources in the Huohuoshan Forest Park area of Guangzhou as an example, the compatibility, coordination and attractiveness of each sound source were classified according to the median (IQR) and mean (SD) of the restorative perceptual evaluation of the compatibility, coherence and attractiveness of the various types of sound sources, as shown in Table 6.…”
Section: Validity Analysismentioning
confidence: 99%